Deciphering Solar Magnetic Activity: 140 Years of the ‘Extended Solar Cycle’ – Mapping the Hale Cycle - McIntosh S.W.; Leamon R.J.; Egeland R.; Dikpati M.; Altrock R.C.; Banerjee D.; Chatterjee S.; Srivastava A.K.; Velli M. (My University, 2025)
We investigate the occurrence of the “extended solar cycle” (ESC) as it occurs in a host of observational data spanning 140 years. Investigating coronal, chromospheric, photospheric, and interior diagnostics, we develop a consistent picture of solar activity migration linked to the 22-year Hale (magnetic) cycle using superposed epoch analysis (SEA) and previously identified Hale cycle termination events as the key time for the SEA. Our analysis shows that the ESC and Hale cycle, as highlighted by the terminator-keyed SEA, is strongly recurrent throughout the entire observational record studied, some 140 years. Applying the same SEA method to the sunspot record confirms that Maunder’s butterfly pattern is a subset of the underlying Hale cycle, strongly suggesting that the production of sunspots is not the fundamental feature of the Hale cycle, but the ESC is. The ESC (and Hale cycle) pattern highlights the importance of 55 ∘ latitude in the evolution, and possible production, of solar magnetism. © 2021, The Author(s).